Perencanaan Strategik Pendidikan Di Dayah Salafi - Nazaruddin Abdullah (Intiqad: Jurnal Agama dan Pendidikan Islam, 2020)
An organization that takes the right procedures and implementation mechanisms on target (strategic), will produce encouraging results. Likewise, an educational institution such as dayah, in an effort to develop a complete human being, of course, must go through a reliable educational process. For this reason, neat strategies and implementation techniques need to be developed, managerial readiness for this is the first priority, provision of facilities as a place for activities that can support the educational process is an inseparable part, recruiting competent teachers or teaching staff, preparing curriculum learning and roster or a schedule of various activities both in the fields of education, worship, skills, everything must be well coordinated. To find out the level of success, evaluation must be held so that it can be anticipated and corrected for weaknesses or deficiencies so as not to be repeated back. Strategic educational objectives in such a way as to achieve encouraging outputs for both institutional managers and stakeholders.